A insustentabilidade do acordo de renegociação da dívida pública interna do município de São Paulo com o Governo Federal - González, Javier Ignácio Toro (2009)
This paper analyzes the assumption and refinancing agreement of the internal public debt held by the Municipality of Sao Paulo with the brazilian Federal Government as signed in May 2000. The first chapter presents the theoretical basis of the economic policy, especially the fiscal policy, adopted by Brazil in the 1990 s and also presents the context that led to the refinancing agreement and to the Law of Fiscal Responsibility. In the second chapter the strategic role of the city of Sao Paulo in Brazil s national economy is discussed as well as the behavior of its public finances since 1995. In the third and final chapter the terms and conditions of the agreement itself as well as its sustainability are analyzed. The results point to the unsustainability of the agreement under the two approaches adopted: the Accounting and the Present Value. It is evident that the agreement - which forbids new indebtedness - harms the ability of the Municipality of Sao Paulo to perform as an entrepreneur of new projects in infrastructure, essential for a modern metropolis like Sao Paulo to meet the challenges it faces, and preventing it from fully exercising its role as a Global City in the greater context of the national Brazilian economy